Antecedents of Financial Management Behavior among Indonesian University Students: The Mediating Role of Perceived Usefulness of Fintech - Indah Desi Sutriani; Willy Abdillah; Chairil Afandy (AIBPM Publisher, 2026)
The rapid growth of financial technology (fintech) among Indonesian university students has reshaped financial transactions, yet it has not always led to prudent financial management practices. This study examines the influence of financial literacy and financial socialization on financial management behavior, with perceived usefulness of fintech as a mediating variable. A quantitative approach was used, with survey data collected from 309 valid responses from undergraduate students in Indonesia who actively use fintech. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings show that financial literacy (? = 0.216, p 0.05) and financial socialization (? = 0.431, p 0.05) have positive and significant effects on financial management behavior. Perceived usefulness of fintech also has a positive and significant effect on financial management behavior (? = 0.252, p 0.05), contrary to the hypothesized negative relationship. The mediation analysis further shows that perceived usefulness of fintech partially mediates the relationships between financial literacy and financial management behavior and between financial socialization and financial management behavior. These findings suggest that perceived usefulness of fintech strengthens financial management behavior among Indonesian university students.